Analisis Nilai California Bearing Ratio (CBR) Terhadap Tebal Lapisan Jalan Tambang pada Pit Selatan PT. Bina Sarana Sukses Site PT. Baramulti Suksessarana - Lucia Litha Respati; Sahrul Ramadhana; Revia Oktaviani; Agus Winarno; Windhu Nugroho (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Mining roads play an important role in supporting the smooth running of mining activities, especially in the process of transporting materials. The bearing capacity of the soil as a road subgrade greatly affects the stability and resistance of the road to heavy equipment loads. This study aims to analyze the effect of the plasticity index and compaction parameters on the California Bearing Ratio (CBR) value, as well as to determine the thickness of the road layer based on the laboratory CBR value. Testing was carried out at the South Pit of PT. Bina Sarana Sukses site PT. Baramulti Suksessarana with a field test method using the Dynamic Cone Penetrometer (DCP) and laboratory tests such as proctor tests, Atterberg limit tests, and CBR tests on various variations of clay and sand soil mixtures. The results showed that increasing the plasticity index decreased the CBR value, while increasing the maximum dry density and decreasing the optimum water content increased the CBR value. Based on the laboratory CBR value, recommendations were obtained for the appropriate road layer thickness to ensure optimal bearing capacity for heavy equipment passing through the research area.